2000
DOI: 10.2460/javma.2000.217.1689
|View full text |Cite
|
Sign up to set email alerts
|

Career racing performance in Thoroughbreds treated with prosthetic laryngoplasty for laryngeal neuropathy: 52 cases (1981–1989)

Abstract: In addition to warning clients of the complications associated with prosthetic laryngoplasty, it may be prudent to provide a guarded prognosis for full restoration of racing performance in older horses, unless they are especially talented and are free of other racing-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
4
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 18 publications
10
94
4
3
Order By: Relevance
“…If it can be assumed that these yearlings received the best available care, these data suggest that current surgical treatments cannot fully restored athletic performance in elite racing Thoroughbreds with RLN. This conclusion is supported by another studies (Strand et al 2000). However, a more recent study suggests that prosthetic laryngoplasty combined with ipsilateral ventriculocordectomy restores racing performance in Thoroughbred horses with grade 3 but not grade 4 RLN (Witte et al 2009).…”
Section: Laryngeal Reinnervationsupporting
confidence: 73%
“…If it can be assumed that these yearlings received the best available care, these data suggest that current surgical treatments cannot fully restored athletic performance in elite racing Thoroughbreds with RLN. This conclusion is supported by another studies (Strand et al 2000). However, a more recent study suggests that prosthetic laryngoplasty combined with ipsilateral ventriculocordectomy restores racing performance in Thoroughbred horses with grade 3 but not grade 4 RLN (Witte et al 2009).…”
Section: Laryngeal Reinnervationsupporting
confidence: 73%
“…All the horses showed less dysphagia following to the minimal invasive therapy. Alsobronchitis nach Laryngoplastik zu nennen (Greet et al 1979;Huskamp 1980;Russell und Slone 1994;Röcken und Feyh 1995;Abeele et al 1997, Stick et al 1999Strand et al 2000). Als Ursache für diese Dysphagie wird neben einer sog.…”
Section: Transendoscopic Implant Injection Therapy Of Soft Palate Andunclassified
“…Neben der Epiglottis-Hypoplasie und den "kleinen" Gaumenspalten (Ohnesorge et al 2002) stellen auch postoperative Komplikationen nach Laryngoplastik ein bisher nicht befriedigend gelöstes therapeutisches Problem dar. So wird die Häufigkeit einer postoperativen Aspirationsbronchitis nach Laryngoplastik mit 5 bis 10% angegeben, ohne dass dafür ein schlüssi-ges Behandlungskonzept besteht (Stick et al 1999;Huskamp und Böckenhoff 1978;Huskamp 1980;Greet et al 1979;Russell und Slone 1994;Röcken und Feyh 1995;Strand et al 2000;Abeele et al 1997). Selbst die Entfernung des Fadens führt nicht in allen Fällen zum Abklingen der Dysphagie, beinhaltet aber das Risiko, einer erneuten Stenose durch einen herabsinkenden Aryknorpel (Stick et al 1999;Tulleners et al 1988b;Greet et al 1979).…”
Section: Diskussionunclassified
“…Prosthetic laryngoplasty is an accepted surgical procedure for correction of this condition and is frequently performed with little variation of the original technique first described by Marks et al Additional reported techniques for addressing a paralyzed arytenoid cartilage include neuromuscular pedicle graft, nerve transplant, nerve anastomosis, and arytenoidectomy . Reported success rates for a return to performance after prosthetic laryngoplasty in racing breeds ranges from 45 to 78% …”
mentioning
confidence: 99%